METHODS FOR MEASURING PARAMETERS IN AVIATION. - Kadirova Sharofat Abduvaxobovna; Ismatova Ozoda Normatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: Parameter measurement accuracy (measurement error value), measurement range, its sensitivity, size and other important parameters of technical equipment belonging to the aviation field, measurement of the parameter necessary for the operation of the system about methods. This article provides some ideas on how to measure parameters in aviation.